Investigating the isolated effects of a soccer-specific mental fatigue manipulation on different task types - Weiler, Helena; Ennigkeit, Fabienne; Altmann, Stefan; Steindorf, Lena; Spielmann, Jan; Englert, Chris (Frontiers in Psychology, 2025)
IntroductionMental fatigue negatively impacts athletic performance, but commonly employed tasks like the Stroop task often lack ecological validity. This study aimed to validate a modified, soccer-specific Footbonaut task as a mental fatigue manipulation and examine its effects on following tasks representing task-specific, near-, and far-transfer domains.MethodsA randomized, counterbalanced within-subject design was implemented with n = 24 soccer players. Participants completed a Footbonaut task (task-specific), the LSPT (near-transfer), and the Stroop task (far-transfer) before and after mental fatigue manipulation via the Footbonaut.ResultsInconsistencies emerged between interaction effects and post-hoc tests, showing no clear negative effect of the manipulation on accuracy or response times. The employed mental fatigue manipulation did not differentially affect the three tasks, indicating a lack of transfer effects.DiscussionAlthough mental fatigue was not successfully induced by the sport-specific Footbonaut task, the findings emphasize the need for ecologically valid, innovative methods to better understand mental fatigue in sports.